Analysis of agreement between assessment tools for hamstring flexibility in elderly. - Tozim, Beatriz Mendes; Lorenzo, Daniele Moraes de; Furlanetto, Mariana Giglio; Morcelli, Mary Hellen; Navega, Marcelo Tavella (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The aging is characterized by a reduction in the effectiveness of skills, among them the loss of the flexibility. The hamstring muscles may be affected by the decreased flexibility occurs when elderly can present limitation of gait, low back problems and osteomuscular. Among the techniques used to evaluate the flexibility of the hamstring muscles are the Sit and Reach Test and Computerized Photogrammetry evaluation of the popliteal angle . However, the scientific literature doesn’t provide consistent data on the correlation of these forms of evaluation. Objective: To analyze the correlation between the sit and reach test and Computerized Photogrammetry evaluation of the popliteal angle used to assess the flexibility of the hamstring muscles in elderly women. Method: This was a cross-sectional, observational study, consisting of 39 elderly, healthy. The evaluation was composed by forms with personal details and physical examination (body weight, height and body mass index), and the evaluation of tests to measure the flexibility of the hamstring muscles (Sit and reach test and Computerized Photogrammetry evaluation of the popliteal angle). The correlation of the data was done by using the Spearmam’s rank correlation coefficient, with a significance level of 5% (p<0.05). Results: The data showed a positive correlation between Sit and Reach Test Computerized Photogrammetry and the popliteal angle of the right leg (r=0.4690, p=0.0026) and the left leg (r=0.3604, p=0.0241). Conclusion: The data from this study allow conclude that the tests for assessing hamstring flexibility in elderly women, the Sit and Reach Test and Computerized Photogrammetry evaluation of the popliteal angle are complementary because it doesn’t correlate strongly.